A comparative analysis of the conceptual metaphor “war is a wild beast” in the literary works of Wayne Karlin and Chu Lai - Pham, Hang Thu (Edelweiss Applied Science and Technology, 2025)
This study investigates the conceptual metaphor "war is a wild beast" as articulated in Wayne Karlin’s Wandering Souls and Chu Lai’s Red Rain (Mưa Đỏ), with the aim of exploring how metaphor functions as both a cognitive framework and a semiotic mechanism for representing war trauma. Employing a qualitative, interpretive-comparative methodology, the research draws on Conceptual Metaphor Theory, embodied cognition, and semiotic analysis to examine five metaphorical projections—predation, screaming, survival, irreparable wounding, and moral blindness—through which war is cast as an instinctual, amoral, and biologically driven phenomenon. The comparative analysis reveals both convergence and divergence: while Karlin and Chu Lai similarly depict war as a dehumanizing force that reshapes memory, perception, and subjectivity, their metaphorical realizations differ in cultural expression, narrative stance, and figurative intensity. The findings affirm that metaphors are not merely stylistic embellishments, but serve as fundamental cognitive and semiotic structures through which war is conceptualized, narrated, and emotionally processed. This study concludes that metaphor is a powerful interpretive tool for accessing the affective and ethical dimensions of wartime experience. In practical terms, the research provides pedagogical insights for teaching war literature in cross-cultural contexts and highlights the broader applicability of metaphor analysis in fostering empathy, deepening understanding of historical trauma, and enriching interdisciplinary approaches to literary interpretation.